Performance of Percentage Refusal Density (PRD) in Asphalt Concrete – Wearing Course (AC-WC) Mixtures with Silica Sand Substitution as Fine Aggregate - Mukhlis, Mukhlis; Lusyana; Enita Suardi; Denisa Rahma Sukri; Alyza Sazama (IJIMCE : International Journal of Innovation in Mechanical Construction and Energy, 2024)
Indonesia is experiencing significant traffic load growth; however, this is often not matched by the development of adequate road infrastructure. This phenomenon occurs because traffic load growth is faster than the development of road infrastructure. Excessive traffic load can cause damage to the roads. Aggregates, especially fine aggregates, play an important role in flexible pavement layers, particularly in the AC-WC layer. The AC-WC layer aims to provide smoothness, safety, and comfort for road users while protecting the underlying layers from damage caused by traffic loads, such as subsidence, ruts, and asphalt deformation. The use of silica sand has become one alternative to improve the quality of the AC-WC layer. This study aims to obtain the Optimal Asphalt Content (KAO) value and the Refusal Optimal Asphalt Content (KAO) value. The KAO value using the Marshall method in the AC-WC mixture is 5.99% for 0% silica sand variation, 5.88% for 25% silica sand variation, 5.845% for 50% silica sand variation, 5.835% for 75% silica sand variation, and 5.810% for 100% silica sand variation. The Refusal KAO value is 5.920% for 0% silica sand variation, 5.83% for 25% silica sand variation, 5.785% for 50% silica sand variation, 5.750% for 75% silica sand variation, and 5.775% for 100% silica sand variation. Thus, the greater the percentage of silica sand added as a substitute for fine aggregates in the AC-WC mixture, the lower the Marshall KAO and Refusal KAO values obtained.